Clinical audit of methotrexate therapy in psoriasis at a tertiary care teaching hospital in Western India - Anuj Bhut; Jinal Jitendrabhai Tandel; Pragya Ashok Nair (Wolters Kluwer Medknow Publications, 2023)
Background: Methotrexate (MTX) is one of the most useful drugs in the treatment of psoriasis. It is like a double-edged sword; beneficial when given under strict medical supervision and harmful when standard guidelines are not followed. Objective: The present study was a process audit done with the aim to improve quality of care in patients of psoriasis with MTX therapy and to minimize the errors. Materials and Methods: The study was a clinical audit assessing patients of psoriasis who were given MTX therapy. Patients were selected on a random basis from hospital data records from January 2018 to August 2019. To assess the patients on MTX therapy, a pro forma was filled which included demographic details, psoriasis area severity index (PASI) scores, baseline investigations carried before starting MTX and at regular intervals afterward, dosage of MTX, its tapering schedule, and cumulative dose. The data were analyzed using descriptive statistics. Ratios, proportions, and percentages were used to describe the data. Results: A total of 30 psoriasis patients on MTX therapy were selected randomly, of which 25 (83.3%) participants had record of proper history and clinical assessment. PASI >10 was observed in 24 (80%) and was calculated by the 1st-year residents in 15 (50%) participants. Before starting MTX therapy, baseline laboratory investigations (CBC, LFT, and RFT) were done in all 30 (100%) participants. Initial dose of MTX (2.5-5 mg/week) was given in 6 (20%) participants. Supplementary medications such as folic acid in proper dosage were given to 28 (93.3%) participants. Twenty-nine (96.6%) participants were investigated for CBC and LFT every 2 weekly in the first 3 months, while only 16 (53.3%) participants were investigated for RFT. After reduction of 75% of PASI, MTX was tapered in 21 (70%) participants. Conclusion: The study reveals some pitfalls in following the guidelines in patients on MTX. Educational interventions in the form of training among dermatologist and resident doctors should be carried out.